1985
DOI: 10.1007/bf00698288
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular proteins in the dynamics of vasogenic brain edema

Abstract: The relationship between extravasation of proteins into extracellular spaces of brain parenchyma and the water content of such regions were evaluated in an experimental model. In this model, a temporary opening of the blood-brain barrier (BBB) to proteins was produced without significant injury to the cellular elements of brain tissue. Rabbits were subjected to bolus injection of their own blood under 360-400 mm Hg pressure via the internal carotid artery. The opening of the barrier and its duration were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 15 publications
5
30
0
Order By: Relevance
“…25,30,31 Although there is evidence that raised intravascular pressure may compromise the integrity of the blood-brain barrier resulting in "leak through" of intravascular catecholamines, the evidence for this is based on animals studies conducted under conditions that are vastly different from those of the current study, that is, prolonged (hours) periods of extreme hypertension (eg, MAP Ͼ180 mm Hg). 32,33 We acknowledge that new developments in functional MRI will likely provide invaluable insight into how asymmetrical dCA may influence CBF to discreet regions of the brain.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…25,30,31 Although there is evidence that raised intravascular pressure may compromise the integrity of the blood-brain barrier resulting in "leak through" of intravascular catecholamines, the evidence for this is based on animals studies conducted under conditions that are vastly different from those of the current study, that is, prolonged (hours) periods of extreme hypertension (eg, MAP Ͼ180 mm Hg). 32,33 We acknowledge that new developments in functional MRI will likely provide invaluable insight into how asymmetrical dCA may influence CBF to discreet regions of the brain.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Development and resolution of brain edema after stroke has also been shown to parallel the extravasation of plasma-borne proteins [19]; these authors reported that the injured BBB remained open for plasma albumin for about 9 hr after ischemia and brain water accumulation during this period was observed. These reports of increased striatal susceptibility to microvascular damage and edema are in agreement with the present results of striatal hyperemia, increased protein extravasation and incidences of HT.…”
Section: Regional Blood Flow Microvascular Injury and Edema Formationmentioning
confidence: 99%
“…Increased BBB permeability is closely associated with postischemic hyperperfusion in hypercapnia (Fujiwara et al, 1981), hypertension (Johansson and Linder, 1981;Kuroiwa et al, 1985a;Hatashita et al, 1986), and focal ischemia (Tamura et al, 1980). Preventing hyperperfu sion inhibits both BBB opening and brain edema (Ting et al, 1986;Seida et al, 1988;Kuroiwa et al, 1989).…”
Section: Bbb Permeabilitymentioning
confidence: 99%